Faktor Penyebab Rendahnya Motivasi Belajar Siswa Bahasa Inggris Siswa Kelas VIII SMP 18 Raja Ampat - Nuril Kaunain, Safitri; Hidayah, Nur; Dabamona, Miftahulfadlik; Ashari (LPPM IAIN Sorong, 2024)
This study aims to determine the factors that cause low learning interest of SMP Negeri 18 Raja Ampat students in learning English. This study uses a descriptive qualitative method. The study subjects were 45 class VIII A and VIII B students of SMP Negeri 18 Raja Ampat in semester 1 of the 2023/2024 academic year. The data collection techniques used were observation, interviews, and documentation. The results of this study consist of internal and external factors. Internal factors include students' assumptions that English is a complex subject because memorizing a lot of vocabulary and pronunciation in English is quite complicated. External factors include parents' lack of understanding of the importance of students' academic achievement, geographical conditions that can be a barrier for students to go to school, economic factors that make students prefer to skip school to work, and teachers' less interesting teaching methods.